Association between physical inactivity and health-related quality of life in adults with coronary heart disease. (October 2019) - Wardoku, Reginald; Blair, Cindy; Demmer, Ryan; Prizment, Anna
Highlights: Health-related quality of life (HRQoL) is an important health indicator in adults with coronary heart disease (CHD). Physical inactivity was associated with both poor physical and mental HRQol in CHD patients. The association is stronger for physical than mental HRQoL. Abstract: Background: Health-related quality of life (HRQoL) provides an accurate measure of the health status of patients with coronary heart disease (CHD). However, few studies have examined the relationship between physical inactivity and HRQoL in CHD survivors. We evaluated this association in a cross-sectional study of 21, 936 CHD participants in the 2015 Behavioral Risk Factor Surveillance System. Methods: CHD diagnosis, HRQoL and physical activity were self-reported. Physical activity (PA) was categorized (1) based on intensity, into no PA, light to moderate PA and vigorous PA; and (2) based on duration and frequency, into no PA, insufficiently active and active. HRQoL was assessed by the CDC HRQoL questionnaire. Participants with 14+ physical or mental unhealthy days in a 30-day window were grouped into poor physical or mental HRQoL. We estimated the odd ratios (AOR) and 95% confidence intervals (CI) of poor HRQoL associated with PA after adjusting for age, sex, education, income level, social support, smoking status, ethnicity/race, BMI, chronic conditions, and CHD groups. Results: Compared with vigorous PA, adults with no PA had higher odds (95% CI) of poor physical HRQoL [1.82 (1.58, 2.10)] and poor mental HRQoL [1.28 (1.05, 1.55)]. When compared with active adults, AOR (95% CI) for adults with no PA were 1.80 (1.55, 2.01) and 1.17 (0.97, 1.42) for poor physical and mental HRQoL, respectively. Conclusions: We found an association between physical inactivity and poor physical and mental HRQoL among CHD survivors. There is a need for longitudinal studies to determine the temporality of this association.